Design of an under-frequency load shedding scheme in a micro-grid - Vijayan, Navin (2018)
The purpose of this study is to understand the relationship between the system frequency and the total synchronous generator loading and implement an under-frequency load shedding scheme to an existing load frequency control module. The behavior of the system depends on the amount of loading which will then determine if the system frequency deviation is higher or lower than the nominal value of 50Hz. Load frequency control will not be applicable if the frequency deviation is too large. The under-frequency load shedding scheme is a control scheme whereby the loads are shed in several phases depending on the severity of the frequency deviation in the system.